A model experiment: competitive sorption of Cd, Cu, Pb and Zn by three different soils - Veronika ZEMANOVÁ; Lukáš TRAKAL; Pavla OCHECOVÁ; Jiřina SZÁKOVÁ; Daniela PAVLÍKOVÁ (Soil and Water Research, 2014)
The aim of this study was to evaluate and compare the competitive and individual sorption of Cd, Cu, Pb and Zn on three natural soils: a Gleyic Fluvisol (content of Cd 30, Cu 25, Pb 2297 and Zn 3718 mg/kg), a Gleyic Cambisol (content of Cd 5, Cu 29, Pb 1158 and Zn 180 mg/kg) and a Chernozem (content of Cd 0.4, Cu 36, Pb 75 and Zn 67 mg/kg). For evaluation of the sorption and desorption, the Freundlich isotherms were used. The results of the model experiment confirmed that the sorption from single-metal solution was more effective than sorption under multi-metal conditions, due to competitive effects. In all tested soils sorption of Cd, Cu and Zn decreased with the rate of other competitive metals; the Pb sorption was not affected by other competitive metals in solutions. Moreover, during multi-metal sorption, Zn was significantly desorbed in Cambisol. In general, sorptions of Cu, Pb and Zn were greater in uncontaminated soil compared to contaminated soils. Clear trend of impact of the contamination on Cd sorption was not observed. The results showed the sorption decreasing in order Chernozem > Fluvisol > Cambisol. The sorption was the greatest in uncontaminated soil with low mobility of studied metals.